Clinical features of post-COVID period. Results of an International Register "Dynamics Analysis of Comorbidities in SARS-CoV-2 Survivors (ACTIV SARS-CoV-2)" (12-month follow-up) - G. P. Arutyunov; E. I Tarlovskaya; A. G. Arutyunov; Yu. N. Belenkov; A. O. Konradi; Yu. M. Lopatin; A. P. Rebrov; S. N. Tereshchenko; A. I. Chesnikova; H. G. Hayrapetyan; A. P. Babin; I. G. Bakulin; et al. (Российский кардиологический журнал, 2023)
Aim. To investigate on post-COVID period in patients of the Eurasian region.Material and methods. A total of 9364 consecutively hospitalized patients were included in ACTIV registry. Enrollment of patients began on June 29, 2020, and was completed on March 30, 2021, corresponding to the first and second waves of the pandemic. Demographic, clinical, and laboratory data, computed tomography (CT) results, information about inhospital clinical course and complications of COVID-19 during hospitalization were extracted from electronic health records using a standardized data collection form. The design included follow-up telephone interviews with a standard questionnaire at 3, 6, and 12 months to examine the course of post-COVID period.Results. According to ACTIV register, 63% of patients after COVID-19 had new adverse symptoms or exacerbations of the existing symptoms lasting for up to 1 year. After hospital discharge, 79,8% of patients sought unscheduled medical attention in the first 3 months, 79,1% at 4-6 months, and 64,8% at 7-12 months. Readmission rate was 11,8% in the first 3 months, 10,9% at 4-6 months, and 10,1% at 7-12 months. The most common reasons for unscheduled treatment in the first 3 months were uncontrolled hypertension, decompensated type 2 diabetes, destabilization of coronary artery disease, gastrointestinal disease, AF episodes, exacerbation of asthma and chronic obstructive pulmonary disease, decompensated heart failure (HF). The 12-month mortality of COVID-19 survivors after the discharge was 3,08%. Multivariate analysis showed that independent risk factors for fatal outcome were age (direct correlation), the levels of hemoglobin (inverse correlation), oxygen saturation (inverse correlation), and aspartate aminotransferase (direct correlation), as well as class III-IV HF, prior stroke, cancer, inhospital acute kidney injury. Based on these identified risk factors, a nomogram was constructed to determine the 3-month mortality risk after discharge.Conclusion. Analysis of ACTIV register showed that end of the acute phase of COVID-19 does not imply a complete recovery.